2002
DOI: 10.1002/art.10788
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of assistive device usage and user and non‐user characteristics: Long‐handled bath sponge

Abstract: Objectives. To examine use of an assistive device, a long-handled bath sponge (LHBS) in patients with rheumatoid arthritis and osteoarthritis to describe use from the time of in-hospital prescription to the 2-and 12-month followups, and to describe the characteristics of those who became device users and non-users. Methods. Patients (n ‫؍‬ 102) who were prescribed a LHBS during hospitalization were followed prospectively. The clinical and psychosocial assessment included disease, physical and psychosocial fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(20 reference statements)
0
5
0
2
Order By: Relevance
“…In a medical as well as a political perspective, however, the value of providing ADs to patients with certain diagnoses or disabilities may be questioned. Regarding RA, our knowledge is restricted to patients with longstanding disease (5, 7, 10–12). Furthermore, many studies have been restricted to women (11, 13).…”
Section: Introductionmentioning
confidence: 99%
“…In a medical as well as a political perspective, however, the value of providing ADs to patients with certain diagnoses or disabilities may be questioned. Regarding RA, our knowledge is restricted to patients with longstanding disease (5, 7, 10–12). Furthermore, many studies have been restricted to women (11, 13).…”
Section: Introductionmentioning
confidence: 99%
“…The Comprehensive ICF Core Set © CAOT PUBLICATIONS ACE RA clients frequently report limitations in various daily activities that may be significantly improved through the use of assistive devices (Rogers, Holm, & Perkins, 2002;Thyberg, Hass, & NordenskiÖld, 2004). Since the Comprehensive ICF Core Set for RA should be relevant for all health professionals working with clients with RA, it cannot be concluded that this finding indicates a lack of validity.…”
Section: Discussionmentioning
confidence: 99%
“…Since the Comprehensive ICF Core Set for RA should be relevant for all health professionals working with clients with RA, it cannot be concluded that this finding indicates a lack of validity. The Comprehensive ICF Core Set © CAOT PUBLICATIONS ACE RA clients frequently report limitations in various daily activities that may be significantly improved through the use of assistive devices (Rogers, Holm, & Perkins, 2002;Thyberg, Hass, & NordenskiÖld, 2004). Thus, it is not surprising that influencing the use of assistive devices was considered as an important intervention goal by almost all participants.…”
Section: Discussionmentioning
confidence: 99%